The role of media use in the development of discursive citizenship norms among U.S. Latinx - Porten-Cheé, Pablo; Velásquez, Alcides; Muddiman, Ashley (Information, communication & society, 2025)
Aiming to expand current research on the mechanisms and conditions under which novel citizenship norms emerge among different populations, we investigate the antecedents of discursive citizenship norms among Latinx individuals in the United States. Results from a two-wave survey suggest that cross-platform news media repertoires are positively associated with individual information care norms and considered contribution norms. Social media political discussion mediates these relationships. Exposure to negative news covering Latinx communities moderated the association between media repertoires and individual information care norms. Contributions and implications for discursive citizenship norms research are discussed.